Associations between childhood sexual abuse, substance use and body image - Erna Björnsdóttir 1989- (2015)
Abstract Childhood sexual abuse is a very serious but fairly common offense. It is defined as touching and/or non-touching activity, performed by adult or older child. Research has found that childhood sexual abuse can affect adolescent’s substance use. Also has been found that sexual abuse is associated with lower body image. The main purpose of the current study was to investigate the associations between childhood sexual abuse, body image and substance use among adolescents. The possible mediating and moderating effect of body image was also examined. The Icelandic Centre for Social Research and Analysis (ICSRA) collected data for this study as part of their research “Youth in Iceland 2004”. Participants were 9.113 students from 30 secondary schools all around Iceland at the age of 16 and 19 years. The results show that sexual abuse is associated with more substance use and lower body image. The findings also indicate that low body image is associated with more substance use. However, body image had neither mediating nor moderating effect on the relationship between sexual abuse and substance use. Key words; sexual abuse, substance use, body image, adolescents. Abstract – Icelandic Kynferðisleg misnotkun er mjög alvarleg og fremur algengt brot. Kynferðisleg misnoktun er atferli sem framkvæmt er af fullorðnum aðila eða eldra barni sem inniheldur snerting við og eða engin snerting sem þó er talin vera óviðeigandi. Rannsóknir hafa sýnt framá að kynferðisleg misnotkun getur haft áhrif á vímuefnaneyslu unglina og er einnig tengd við lægri líkamsímynd. Meginmarkmið rannsóknarinnar er að kanna tengsl milli kynferðislegar misnotkunar, líkamsímyndar og vímuefnaneyslu meðal unglinga. Hugsanleg miðlunar og samvirknihrif líkamsímyndar voru einnig skoðuð. Notast var við fyrirliggjandi gögn úr rannsókninni Ungt Fólk 2004 sem fengin voru frá Rannsókn og greiningu. Þátttakendur voru 9,113 nemendur við 30 framhaldsskóla viðsvegar um Ísland á aldrinum 16 til 19 ára. Niðurstöður rannsóknarinnar sýndu framá að kynferðisleg ...